Pengaruh Arus Kas Dan Laba Terhadap Harga Saham Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2019 - Esti Veronika; Arie Kawulur (Fakultas Ekonomi Universitas Negeri Manado, 2022)
This study aims to see how much influence cash flow and profit have on stock prices in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2019. This research uses quantitative methods. The data collection technique in this study was purposive sampling and used secondary data which included cash flow, profit and stock prices. The data analysis technique used is multiple linear regression analysis, data processing using Eviews version 9. The results of this study indicate that cash flow has no effect on stock prices because tcount <ttable and probability value> 0.05 so that Ho1 is accepted and Ha1 is rejected and profit has a significant negative effect on stock prices because tcount <ttable and probability value <0.05 so that Ho2 is rejected and Ha2 is accepted.